Assessing the future of trade in the automobile sector between India and Pakistan: Implications of abolishing the negative list - Biswajit Nag (Indian Council for Research on International Economic Relations (ICRIER), 2014)
This paper makes an attempt to understand the implications of trade normalisation between India and Pakistan on the automobile sector. Currently, am majority of auto components are in Pakistan's negative list. Based on both quantitative and qualitative analysis, the paper concludes that India will compete mostly with South-East Asian countries in the Pakistani market, Indian exports will substitute imports from Japan, Thailand and China, and Indian products may not have a significant impact on Pakistan's domestic automobile industry. Besides, opening up trade can create an opportunity for the development of cross border production networks in this sector. This has the potential to provide a major price benefit to Pakistani consumers who will gain substantially from the introduction of new and better models. The paper also identifies the products on which the impact of removal of the negative list is expected to be minimal. In these products, either Pakistan is a small importer from the world or India is not a large exporter to the world, or both. In many other products, Pakistan has been experiencing declining import growth or their share in total import is less than one percent. The threat perception in these products seems to be relatively low. The analysis of India's Revealed Comparative Advantage (RCA) index for automobile products also reflects that India is yet to become competitive in a large number of automobile products and hence, Pakistan does not have an immediate threat in such products. However, there are critical components and vehicle parts in which Pakistan is already a large importer and India will compete with other Asian players in these segments.
Keywords: F10; F13; F14; F50; 330; India-Pakistan; automobile trade; trade normalization; MFN; negative list